Arabic Langguage Teacher’s Skill Level in The Preparation and Use of Teaching Aids in Sekolah Integrasi Rendah Agama JAWI - Zolkapli, Nina Nazliana; Ihwani, Siti Suhaila Ihwani; Abdur Rahim Nasution, Abdul Basit (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
Current educational transformation encourages and demands educators to extensively integrate digital technology during classroom teaching. However, the application skills of digital Teaching Aids (BBM) among Arabic language teachers are still found to be suboptimal compared to the use of conventional teaching aids. Therefore, this study aims to analyze the level skills of teachers in the preparation and using Teaching Aids (BBM) in learning and facilitatiom (PdPc) for the Arabic language subject at Sekolah Integrasi Rendah Agama Jawi (JAWI). In this study, the researcher focuses on analyzing the level of teacher’s skills in the preparation and use of BBM in PdPc for the Arabic language subject at SIRAJ. This study is a survey study involving 53 teachers was teach Arabic language from 5 SIRAJ school.The study instrument was developed by the researcher. The data was analyzed using IBM Statistical Package for the Social Sciences (SPSS) version 30.0 and reported in the form of descriptive statistics that are frequency, percentage and mean. The main result of this study found that the level of teacher’s skills related to BBM is at High level with a mean value reading M=3.95. The overall study shows that the level of teacher’s skills related to BBM in teaching the Arabic language subject is at a high level.
Keywords: Tahap Kemahiran; Penyediaan BBM; Penggunaan BBM; Bahasa Arab; SIRAJ